Analysis of Factors Affecting the Financial Performance of MSMEs Businesses in Buntu Bedimbar Village, Sub-District Tanjung Morawa - Aji Fadillah Saragih; Maya Sari (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to determine the effect of MSME business financial performance on MSME business actors. The type of research used in this research is hypothesis testing. The sample in this study were MSME players in Buntu Bedimbar Village, Tanjung Morawa District. At this time, many MSMEs in the area are declining, both in terms of numbers and income, so for that, the researchers made observations and decided to take several variables that allegedly could affect the business performance of MSMEs in the area. The data collection technique used a questionnaire with 171 respondents. Validity and reliability tests were carried out on respondents who had the same characteristics as the research subjects. The analysis method used in this research is the 1-5 linear scale analysis method. The results showed that the business capital variable had a positive and significant influence on the financial performance of Buntu Bedimbar Village MSME businesses. The business duration variable has no influence and is significant on the financial performance of Buntu Bedimbar Village MSME businesses, the financing variable has an influence and is significant on the financial performance of Buntu Bedimbar Village MSME businesses, the Islamic financial literacy variable has an influence and is significant on the financial performance of Buntu Bedimbar Village MSME businesses. Together, capital, financing, and Islamic financial literacy have a positive and significant influence on the financial performance of Buntu Bedimbar Village MSME businesses, while the length of business does not have any influence on the financial performance of Buntu Bedimbar Village MSME businesses.